EVALUASI SISTEM PEMOTONGAN GAJI DAN SAHAM DALAM PENGELOLAAN PINJAMAN ANGGOTA DI KOPERASI KARYAWAN “MAJU TERUS” SMKS YOHANES XXIII MAUMERE - Maria Stefania Bunga; Andreas Rengga; Kristiana Reinaldis Aek (Jurnal Projemen UNIPA, 2026)
Employee cooperatives play a strategic role as an economic buffer for teachers and school staff, particularly in providing access to safe, transparent, and equitable financial services. This study aims to evaluate the salary and share deduction system in managing member loans at the “Maju Terus” Employee Cooperative of SMKS Yohanes XXIII Maumere. The evaluation focuses on salary deduction procedures for active members, share deduction mechanisms for inactive members, handling of arrears, system effectiveness, obstacles encountered, causes of obstacles, and improvement efforts that have been made. The research method used is a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation studies. The study results show that the salary and share deduction system has been implemented in a structured and effective manner, successfully maintaining the non-performing loan rate below 2% for the past three years, as well as supporting cash flow stability and increasing cooperative revenue. However, the implementation of this system still faces obstacles such as late payment of salary deductions by the school treasurer, insufficient shares of inactive members to cover arrears, a manual recording system, and minimal outreach to new members. Improvement efforts that have been made include monthly coordination meetings, intensive outreach, transparency through membership books, quarterly reporting, and the implementation of moral sanctions. These findings confirm that the salary and share deduction system is not only a loan security tool, but also a concrete manifestation of cooperative values: kinship, collective responsibility, and economic justice.